Application of Lean Manufacturing (5s and Kaizen) to Increase the Productivity in the Aqueous Adhesives Production Area of a Manufacturing Company - Vargas Crisóstomo, Edith Luz (2022)
This research was conducted in a manufacturing company that has been experiencing a low-productivity problem for the last four years in the production area of aqueous adhesives, whose productivity values are lower than the expected value (5 kg/mh). Accordingly, a strategy for improvement based on the Lean Manufacturing methodology was considered necessary in this study, so the Kaizen methodology and the 5S were selected. This was carried out in stages that consisted, first, of a situational diagnosis, followed by the design, implementation and evaluation of the results. These stages were executed in 7 months, from January to July 2019. Upon application of the Lean Manufacturing methodology, the productivity results were evaluated and an average value of 5.58 kg/mh was obtained. It is worth mentioning that in 2018, before the application of Lean Manufacturing, the average productivity value was 4.37 kg/mh.